Efeito de genótipos de sorgo sobre o predador Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) alimentado com Schizaphis graminum (Rondani) (Hemiptera: Aphididae) - Figueira, Liliane K. [UNESP]; Lara, Fernando M. [UNESP]; Cruz, Ivan (My University, 2002)
The work aimed to evaluate the indirect effect of sorghum genotypes resistance on biological aspects of the predator Chrysoperla externa (Hagen) using the aphid Schizaphis graminum (Rondani) as prey. The genotypes used in the study were: GR 11111 and TX 430 x GR 111 (resistant), GB 3B (moderately resistant) and BR 007B (susceptible). Newrly hatched larvae were confined individually in glass vials and fed on S. graminum reared separately in each one of the four genotypes. After emergence, adults from each treatment were paired in cages and provided with yeast and honey. The insects were observed daily from immature phase until 60 days after adult emergence. Increases on genotype resistance rate promoted higher consumption of aphids by the predator and lesser weight. Lower larval weight, pre-pupal survival and adult longevity of the predator were verified when the aphids were reared on the genotype GR 11111. Beneficial association was observed among the predator C. externa and the resistant genotype TX 430 x GR 111 and among the predator and the moderately resistant GB 3B, thus indicating the possibility of integration between the two methods of control: host plant resistance and biological control.
Effect of sorghum genotypes on the predator Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) fed on Schizaphis graminum (Rondani) (Hemiptera: Aphididae)
Keywords: Aphid; Host plant resistance; Insecta; Integrated control; Sorghum bicolor